Is Group Productivity Loss the Rule or The Exception? Effects of Culture and Group-Based Motivation - Erez, Miriam; Somech, Anit (Academy of Management Journal, 1996)
This study examined four causes of group performance loss: goal specificity, communication, incentives for goal attainment, and high versus low cultural collectivism. Subjects were managers from Israeli kibbutzim (63 individuals) and cities (59 individuals) who worked on a simulated task requiring them to evaluate résumés. We used a two-by-three-by-four design in which sample, goal, and test condition were varied to test hypotheses. Group performance loss occurred only for urban respondents with a do-your-best goal and team task.